Intracellular Tenofovir-Diphosphate and Emtricitabine-Triphosphate in Dried Blood Spots Following Tenofovir Alafenamide: The TAF-DBS Study. (1st July 2020) - Yager, Jenna; Castillo-Mancilla, Jose; Ibrahim, Mustafa E.; Brooks, Kristina M.; McHugh, Cricket; Morrow, Mary; McCallister, Scott; Bushman, Lane R.; MaWhinney, Samantha; Kiser, Jennifer J.; Anderson, Peter L.
Abstract : Background: Tenofovir alafenamide (TAF), in combination with FTC, was recently approved for PrEP in the United States. The objective of this study was to assess the relationship between tenofovir-diphosphate (TFV-DP) and emtricitabine-triphosphate (FTC-TP) in dried blood spots (DBS) with adherence to TAF/FTC. Methods: TAF-DBS was a randomized, crossover clinical study of TFV-DP in DBS, following directly observed dosing of 33%, 67%, or 100% of daily TAF (25 mg)/FTC (200 mg). Healthy volunteers were randomized to 2 different, 12-week dosing regimens, separated by a 12-week washout. DBS were collected weekly. TFV-DP and FTC-TP were extracted from two 7-mm punches and assayed with LC-MS/MS. Results: Thirty-seven participants (17 female, 7 African American, and 6 Hispanic) were included. TFV-DP exhibited a mean half-life of 20.8 days (95% confidence interval: 19.3 to 21.3). The slope for TFV-DP versus dosing arm was 1.14 (90% confidence interval: 1.07 to 1.21). The mean (SD) TFV-DP after 12 weeks was 657 (186), 1451 (501), and 2381 (601) fmol/2 7-mm punches for the 33%, 67%, and 100% arms. The following adherence interpretations are proposed: <450 fmol/punches, <2 doses/wk; 450–949 fmol/punches, 2–3 doses/wk; 950–1799 fmol/punches, 4–6 doses/wk; and ≥1800 fmol/punches, 7 doses/wk. FTC-TP was quantifiable for 1 week after drug cessation in 50%, 92%, and 100% of participants in the 33%, 67%, and 100% arms, respectively. Conclusion: TFV-DP in DBS after TAF/FTC exhibited a long half-life and was linearly associated with dosing, similar to its predecessor tenofovir disoproxil fumarate. FTC-TP was quantifiable for up to 1 week after drug cessation. Together, these moieties provide complementary measures of cumulative adherence and recent dosing for TAF/FTC. Abstract : Supplemental Digital Content is Available in the Text.